2016
DOI: 10.1016/j.artmed.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic-induced dyskinesia assessment based on a single belt-worn accelerometer

Abstract: Background: After several years of treatment, patients with Parkinson's disease (PD) tend to have, as a side effect of the medication, dyskinesias. Close monitoring may benefit patients by enabling doctors to tailor a personalised medication regimen.Moreover, dyskinesia monitoring can help neurologists make more informed decisions in patient's care.Objective: To design and validate an algorithm able to be embedded into a system that PD patients could wear during their activities of daily living with the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 33 publications
0
34
0
1
Order By: Relevance
“…Notably, the algorithmic basis for the detection of bradykinesia in [53] and this work, with some modifications, is based on a previous work by the authors [52]. On the other hand the algorithmic basis of the dyskinesia block is based on another previous work [33]. The way to combine these algorithms and the database where they are validated are completely new.…”
Section: Signal Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the algorithmic basis for the detection of bradykinesia in [53] and this work, with some modifications, is based on a previous work by the authors [52]. On the other hand the algorithmic basis of the dyskinesia block is based on another previous work [33]. The way to combine these algorithms and the database where they are validated are completely new.…”
Section: Signal Processing Methodsmentioning
confidence: 99%
“…More concretely, these works mainly rely on the use of inertial sensors, although there are other less extended alternatives, as the use of sEMG [25,26,27,28] or another physiological measure [29]. The majority of these research studies have employed wearable sensors to study specific PD symptoms such as FOG [30,31,32], dyskinesia [33,34,35,36] and bradykinesia [18,19,22,37,38,39]; thus, the aim was detecting the presence or severity of a certain symptom. However, the main objective of our work is the detection of ON/OFF motor states of patients, which is mainly related to a dopaminergic deficit and is not related to the presence of a unique symptom.…”
Section: Related Workmentioning
confidence: 99%
“…These algorithms have been previously presented by the authors in other works [3,41,60,61,62,63]. With these classifiers, along with the gait analysis algorithm, an identification of the PD motor state can be performed.…”
Section: Firmwarementioning
confidence: 99%
“…In our previous works [3,41,61,65], sampling frequency was 40 Hz. This frequency was selected due to two reasons: the first one, it has been shown that 40 Hz is enough to measure human movement [49]; second, due to the maximum frequency of interest within the PD movements, which is 20 Hz for walking activities [61]. Regarding the filter, a 2nd order Butterworth low-pass filter has been employed to remove the noise of the signal.…”
Section: Firmwarementioning
confidence: 99%
See 1 more Smart Citation